Hemoglobin patterns in different populations of Synbranchus marmoratus Bloch, 1795 (Pisces, Synbranchidae) - Nakamoto, Wilson [UNESP]; Machado, Paulo Eduardo de Abreu [UNESP]; Foresti, Fausto (Elsevier B.V., 1986)
1. 1. Total hemolysates of Synbranchus marmoratus Bloch, 1795 captured at four different sites in the State of São Paulo, Brazil, showed two different hemoglobin phenotypes when submitted to agar-starch gel electrophoresis on glass slides in basic buffer. 2. 2. Phenotype I was characterized by 3 hemoglobin bands. When the total hemolysate was submitted to cellulose acetate electrophoresis in basic buffer containing 6 M urea and β-mercaptoethanol, Phenotype I showed four globins of the α 1, α 2, β and γ types, with 11.9 ± 1.9 g% total hemoglobin, 45.3 ± 3.6% globular volume, and 26.8 ± 4.4% mean corpuscular hemoglobin concentration (MCHC). 3. 3. Phenotype II showed three groups of hemoglobins, with a total of up to 12 hemoglobin bands. When the total hemolysate was submitted to cellulose acetate electrophoresis in basic buffer containing 6 M urea and β-mercaptoethanol, phenotype II showed five types of globins, denoted types α 1, α 2, γ 1, γ 2 and β, having electrophoretic positions different from those of Phenotype I globins, with 18.1 ± 3.3% total hemoglobin, 47.9 ± 6.4% globular volume, and 37.8 ± 4.4% MCHC. 4. 4. The distribution of the specimens having the two hemoglobin phenotypes is associated with the different geomorphological provinces of the State of São Paulo, suggesting the existence of at least two populational groups of Synbranchus marmoratus. © 1986.
Keywords: Fresh water; Hemoglobin; Animal; Blood; Brazil; Comparative study; Demography; Electrophoresis; Fish; Genetics; Karyotyping; Animal; Comparative Study; Demography; Electrophoresis, Cellulose Acetate; Fishes; Fresh Water; Hemoglobins; Karyotyping; Support, Non-U.S. Gov't